Nablus Municipality new building - Hantoli, Asim; Melhim, Anas; Hantoli, Nedal (My University, 2021)
This project introduces the integration between varies engineering specialization such as the architectural, civil, electrical, mechanical, HVAC, and environmental engineering, etc. while it was hard to integrate all this engineering specialization in one facility and to satisfying the all discipline but now that will be our goal in this project. Nablus municipality located at the down town near of Nablus mall which contain the parking of the interior public transportation for its importance. This proposed design was prepared by an architectural student which was studying at the faculty of engineering in An-Najah National University. The general shape of the facility like a key shape. And because the designer is an architectural designer, the focus was on the architectural aspect over the other aspects, so in our role as building engineers we will concerned on other aspects such as the structural, environmental, electrical, mechanical, etc. And we will be as a literature review for municipalities design requirements. Different case studies a world will be presented. And based on that literature review an extensive revision of the proposed municipality will be done. This will help us to identify to what extent that design complies with municipality's standards and requirements, as illustrated in the literature part. Then a conceptual structural system will be proposed also. The structural design of the building will be detailed in addition to the seismic design work according to international standards In addition to making a detailed economic bill for the building.